Gallbladder Mucus Plug Mimicking Ascaris Worm: An Ambiguous Cause of Biliary Colic. (26th November 2017) - Termos, Salah; Alali, Mohammad; Alkabbani, Majd; AlDuwaisan, Abdullah; Alsaleh, Ahmad; Alyatama, Khalifa; Hayati, Hussein
Abstract : Biliary colic is a visceral pain caused by attempts of the gallbladder or bile duct to overcome the obstruction in the cystic duct or ampulla of Vater. Obstruction can be due to different etiologies such as stone, mass, worm, and rarely by mucus plug. We report the case of a 31-year-old gentleman who presented with recurrent biliary colic and weight loss. Work-up showed linear calcifications in the gallbladder extending to the common bile duct suggesting hepatobiliary ascariasis. Further investigations including stool analysis, upper endoscopy, endoscopic ultrasonography (EUS), and endoscopic retrograde cholangiopancreatography (ERCP) did not support our provisional diagnosis. Laparoscopic cholecystectomy was performed. Histopathological finding was grossly ambiguous; a rope-like mucus plug resembling ascaris worm was noted. The patient's condition improved instantly after the procedure. To our knowledge, we are reporting the first case in the English literature describing this unique entity of symptomatic gallbladder disease to increase awareness and improve its management.